Vulnerabilities of waste scavengers to COVID-19 impacts: outcomes of an exploratory study in Ghana - Debrah, Justice Kofi (2022)
The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2022